Parameters and Measurement Techniques of Reconfigurable Intelligent Surfaces - Biswarup Rana; Sung-Sil Cho; Ic-Pyo Hong (Micromachines, 2022)
Reconfigurable intelligent surface (RIS)-aided wireless communications systems are one the promising wireless communication system where the wave can be guided by the RIS. It is envisioned that beyond-5G/6G communication will have a low-cost, high spectral efficiency, high energy efficiency, and smart wireless environment. In this paper, initially, different measurement techniques of the RIS have been discussed, which are available in the literature. Then, a new type of RIS has been proposed. Finally, a different parameter measurement technique for our proposed RIS has been presented. A low-cost FR4 substrate with a height of 1.6 mm was considered to design the RIS in the sub-6 GHz frequency band. Another important thing is that our proposed IRS is a single-layer substrate backed by a copper plate. The area of each unit cell was 42 mm × 42 mm. The RIS was designed to operate at the central frequency of the 3.5 GHz frequency band. The novelty of the proposed RIS is that it is a polarization-independent structure. Thus, polarization-related losses can be overcome using this structure. A 10×10-unit cell array was designed to check the radiation performance. The magnitude of the reflection coefficients was measured in our laboratory for the proposed configuration.